Charging and Discharging Process Analysis of Energy Management System Strategy Towards Battery Aging in Series Configuration Hybrid Vehicle - Alim, Aditya Halaqul; Sudarmanta, Bambang (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
Batteries, crucial for hybrid and electric vehicles, inevitably experience capacity loss over time due to regular usage, known as battery aging. The degradation is influenced by factors like the C-rate, depth of discharge (DOD), and temperature variations. This study delves into a hybrid series-configured vehicle that integrates both a battery and an engine-generator as primary energy sources. The primary objective revolves around determining an optimal energy management system (EMS) that mitigates battery aging effects. Testing was conducted across varying speeds: 17 km/hour, 30 km/hour, and 50 km/hour, involving two operational modes—full electric and hybrid. The engine-generator activation was contingent upon the battery's state of charge (SOC) set at 40% and 60%, operating consistently at 7000RPM and 7500 RPM. Data collected from these experiments facilitated the assessment of battery aging, simulated through MATLAB Simulink software. The findings highlighted that the most favorable battery aging occurred at 50 km/hour, when the engine-generator was engaged at 60% SOC and operated at an engine speed of 7500 RPM. Notably, the hybrid mode showcased superior battery longevity, particularly at higher speeds.